KAJIAN KEAMANAN ANTIHIPERTENSI PASIEN GAGAL GINJAL KRONIK LANJUT USIA DI UNIT HEMODIALISA RSUP DR. SARDJITO YOGYAKARTA - Setyaningrum, Ndaru; Pramantara, I Dewa Putu (Indonesian Research Gateway)
ABSTRACT : The growth of elderly population increase fastest among the other age group. The elderly population been related to decrease renal function and other comorbidity as consequence of aging. The aim of this study is to know how about adverse drug reaction (ADR) and potential interaction of antihypertension drug in chronic kidney disease patient. This is a descriptive study about elderly patient with chronic kidney disease on period October 22th 2012 – January 22th 2013. This study use Naranjo scale to evaluate ADR and Tatro Drug Interactions Fact to evaluate potential drug interaction. There were 38 subjects analized, age < 70 years old (24 patients) and ≥ 70 years old (14 patients); gender men (26 patients) and women (12 patients); duration hemodialysis < 8 months (8 patients) and ≥ 8 months (30 patients); comorbidity DM (23 patients) and non DM (15 patients). There were probable ADR 4 events (10,8%) consist of nifedipine (2 events), lisinoprile (1 event) and captoprile (1 event). There were 14 events (37,8%) potential drug interactions consist of minor interaction (12 events) 32,4% and major interaction (2 events) 5,4%. This study show that there were actual probable ADR 10,8% and potential drug interaction 37,8%.